Effect of dialysis on plasma and CSF tryptophan and CSF 5-hydroxyindoleacetic acid in advanced renal disease. Issue 8 (August 1980) - Sullivan, P A; Murnaghan, D; Callaghan, N; Kantamaneni, B D; Curzon, G
Abstract : Patients with uraemic encephalopathy were previously found to have low total tryptophan (bound plus free), but high free tryptophan concentrations in the plasma and high CSF tryptophan concentrations. The 5-hydroxytryptamine metabolite 5-hydroxyindoleacetic acid was also raised in the CSF. A study of the effect of dialysis treatment on these substances in chronic uraemic patients with and without dialysis dementia is described. After an episode of dialysis the patients without dialysis dementia showed increased plasma total tryptophan and decreased free tryptophan. These changes were associated with a decrease of plasma free fatty acid. The patients with dialysis dementia did not show changes in tryptophan, but plasma free fatty acid rose. CSF concentrations of 5-hydroxyindoleacetic acid fell moderately in both groups of patients on dialysis.